Identificação de QTLs candidatos associados à qualidade pós-colheita do pedúnculo de caju. - Santos, Francisco Herbeth Costa dos (2008)
Detection of quantitative trait loci (QTLs) and marker assisted selection associated with theses QTLs have shown a great interest in breeding programs focused on fruit quality traits. The aim of this work were to study the quality of cashew apple in several genotypes and identify QTLs associated with these traits, using the cashew genetic maps already developed. For the physical and physical-chemical analyses, it was collected 15 cashew apple per plant, from 66 genotypes of the generation F1 originated from the cross CCP 1001 x CP 96 and from the clone CCP 76, used as a control. The following characteristics were evaluated: color (lightness, redness and yellowness), weight (whole, nut and apple), apple length and diameter (upper and lower), oligomeric phenolic, total soluble solids (TSS), total titratable acidity (TTA), TSS/TTA ration and vitamin C. Detection of candidate QTLs were realized using the methods non-parametric mapping, interval mapping and multiple QTL mapping. The results evidence high phenotypic variability in the generation F1 for all characters analyzed, with potential for the selection of genotypes with the best characteristics for fresh fruit market. The QTL analyses showed 54 QTLs associated with quality of cashew apple. The characteristic redness presented the lowest number of QTL (two), while apple weight demonstrated the highest number (seven). These QTLs explained 3.15 to 21.33 % of the total phenotypic variance. The results strongly support the presence of true QTLs. These QTLs are in the process of validation to be used in the marker assisted selection in cashew breeding programs.